The health, financial and relationship wellbeing of Australian couples: Does marriage matter? - Bencic, L; Parker, R (My University, 2008)
A large body of literature attests to a range of differences between married and unmarried couples. Collectively, the research points to married people being happier, healthier and better off financially than those not married. One conclusion drawn from this data is that marriage in and of itself confers a range of benefits on married couples that the not-married do not enjoy. However, there are certain flaws in the way in which much of the research is conducted, in particular the groups against which comparisons are made. Typically, married participants are compared to those who are single (never married), separated, divorced or widowed, and the findings generally support the notion that being in a couple relationship is 'better' than not being coupled. De facto (cohabiting) couples are often not included in such research as a discrete comparison group, thus not allowing for the exploration of the benefits or otherwise of different types of couple relationships. Since couples in de facto relationships vary from legally married couples in terms of their demographic profile, and from each other with respect to their commitment to their partner treating them as a homogeneous group, or including them with married participants for the purposes of analysis, may confound the findings. As the initial step in the ongoing exploration of the relationships of the couples participating in LSAC, this paper reports on comparisons of married, de facto and single/sole parents with respect to their health, and their financial and (for coupled parents) relationship wellbeing. Aspects of these three domains will be compared for the parents of infants and the parents of kindergarten-aged children at waves one and two.
Keywords: Relationships -- Marriage; Relationships; Families and relationships; Relationships; Marriage; Families and relationships